Wiederaufleben der deutsch-französischen Partnerschaft? Eine Bestandsaufnahme im doppelten Wahljahr 2017 - WERNERT, YANN (Rocznik Integracji Europejskiej, 2018)
This article argues that the relations between France and Germany have gained a new dynamic since the French elections of 2017. While president Macron shares more common views with the German left, he will most likely accommodate with conservative parties as well. European reforms have to be expected in the fields of finance, social and defence policy.